IMPLEMENTASI PERATURAN WALI KOTA PEKANBARU NOMOR 24 TAHUN 2013 TENTANG PENYELENGGARAAN REKLAME DI KOTA PEKANBARU (STUDI KASUS PAPAN REKLAME DI JEMBATAN PENYEBERANGAN ORANG KOTA PEKANBARU - Vikha Octafiola; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The placement of billboards has a major influence on urban life because the billboard media is often the place where information can be delivered effectively. The reality of billboards in JPO is very disturbing for users of pedestrian bridges because of the large billboards that are not in accordance with the less well maintained JPO Pekanbaru.This study aims to determine the Implementation of Mayor Regulation Pekanbaru Number 24 of 2013 on the Implementation of Reklame In Pekanbaru City (Case Studies Bulletin Board At the Crossing Crossroads of Pekanbaru City). Theoretical concept of the researcher is the implementation of the policy by using the Mazmanian and Sabatier theory by looking at the data obtained will be discussed thoroughly based on the fact that the institution or research office is implemented. Then compared with the concept and theory that support. The research method used is qualitative research with descriptive data assessment. In the data collection, researchers used interview techniques, observations, and documentation set based on Snowball sampling.Based on the results of research show that not yet opimal this is seen there are deficiencies, there are many billboards that pairs in JPO that JPO own conditions are not good and many are not feasible and JPO development is not in accordance with the criteria. The factors that influence this research are poor communication, lack of public participation and attitude of executor.Keywords: Implementation, Policy, People Crossing Bridge